Effect of Drought on the Growth, Yield and Yield Componants of Paddy in the Purulia District of West Bengal - Bhattacharya, S.N. (Journal of Soil and Water Conservation, 2022)
Out of 200,000 hectares of upland in Purulia District (West Bengal) under paddy the irrigated area is only 1,500 hectares. The average rainfall is 1225 m.m. between June to October and its yearly and monthlly distribution is very irregular. The topography of land is undulated in nature arid soil do not hold euongh moisture to sustain productivity during drought period. For the proper exploitaion of these land the present work as detailed below was undertaken to findout some paddy varieties which can stand severe moisture stress.